Hallazgo del género trigonobalanus forman, 1962 (fagaceae) en el neotrópico-ii (1980)
Morphological, ecological and phenological information is given for the Colombian species Trigonobalanus excelsa G. Lozano, J. Hernández and amp; J. Henao (Fagaceae, Trigonobalanoideae). It is concluded that T. excelsa is a remnant of an old Laurasian lineage that was probably established in America during the Late Cretaceous or Early Tertiary. Possibly this genus, together with Quercus, are members of a Plio-Pleistocene coenochron that arrived from Middle America to the Colombian Andes and still survives in moist with high climatic equability.